Comparisons of Performance of Non-Governmental Organization and Gram Panchayats in Disaster Management - Debabrata Mondal , Sarthak Chowdhury and Debabrata Basu, (Indian Journal of Extension Education, 2016)
Disasters like floods, cyclones, droughts and earthquakes are increasing in India and in almost all parts of the earth due toenvironmental degradation, deforestation, increasing population, global warming, nuclear explosions, and air pollution.There is also worldwide concern to mitigate the growing incidence of disaster and their toll on human life, property, andenvironment. The role of Panchayats (local self governing institutions) is important in view of their proximity to the localcommunity, coverage and engaging people's participation on an institutionalized basis. NGOs are organizations that arenonprofit making, voluntary and independent of government, engaged in activities concerning various societal anddevelopmental issues. The role of the NGOs during a disaster is to have quick response and to try and save as many lives asit can with the given funds. Astudy was undertaken in cyclone Aila affected areas in West Bengal on analysis of the role ofNon Governmental Organization and Gram Panchayats on disaster management. The main role performed by the NGOswere providing relief materials, organizing health camp, involved in rescue operation, arranging temporary shelters andso on. On the other hand the major functions of G.P during the post-disaster were identification of victims forcompensation, relief and rehabilitation work, monitoring and supervision of relief works as well as damage assessment.The data were collected in the month of October 2013 to March, 2014 to attain the objective of the study. A total 150respondents were selected purposively as the respondents. The data were processed into percentage, mean score and ttest. The findings of the study indicated that, the people of the disaster affected area should inform the details of thedisaster sufficiently ahead.